A randomised trial comparing the clinical effectiveness of different emergency department healthcare professionals in soft tissue injury management - Jonathan Richard Benger; Jane Powell; Fiona Cramp; Carey Middleton McClellan (BMJ Open)
Objectives To evaluate the clinical effectiveness of soft tissue injury management by emergency nurse practitioners (ENPs) and extended scope physiotherapists (ESPs) compared to the routine care provided by doctors in a UK emergency department (ED).Design Randomised, pragmatic trial of equivalence.Setting One adult ED in England.Participants 372 patients were randomised; 126 to the ESP group, 123 to the ENP group and 123 to the doctor group. Participants were adults (older than 16 years) presenting to the ED with a peripheral soft tissue injury eligible for management by any of the three professional groups. Patients were excluded if they had any of the following: injury greater than 72 hours old; systemic disease; dislocated joints; recent surgery; unable to give informed consent (eg, dementia), open wounds; major deformities; opiate analgesia required; concurrent chest/rib injury; neurovascular deficits and associated fracture.Interventions Patients were randomised to treatment by ESPs, ENPs or routine care provided by doctors (of all grades).Main outcome measures Upper-limb and lower-limb functional scores, quality of life, physical well-being, preference-based health measures and the number of days off work.Results The clinical outcomes of soft tissue injury treated by ESPs and ENPs in the ED were equivalent to routine care provided by doctors.Conclusions As all groups were clinically equivalent it is other factors such as cost, workforce sustainability, service provision and skill mix that become important. This result validates the role of the ENP, which is becoming established as an integral part of minor injuries care, and demonstrates that the ESP should be considered as part of the clinical skill mix without detriment to outcomes.ISRCTN-ISRCTN trials register number 70891354.